Formulation of gastroretentive floating drug delivery system using hydrophilic polymers and its in vitro characterization - Venkata Srikanth Meka; Senthil Rajan Dharmanlingam; Venkata Ramana Murthy Kolapalli (Universidade de São Paulo, 2014)
The aim of the present research is to formulate and evaluate the gastroretentive floating drug delivery system of antihypertensive drug, propranolol HCl. Gastroretentive floating tablets (GRFT) were prepared by using a synthetic hydrophilic polymer polyethylene oxide of different grades such as PEO WSR N-12 K and PEO 18 NF as release retarding polymers and calcium carbonate as gas generating agent. The GRFT were compressed by direct compression strategy and the tablets were evaluated for physico-chemical properties, in vitro buoyancy, swelling studies, in vitro dissolution studies and release mechanism studies. From the dissolution and buoyancy studies, F 9 was selected as an optimized formulation. The optimized formulation followed zero order rate kinetics with non-Fickian diffusion mechanism. The optimized formulation was characterised with FTIR studies and observed no interaction between the drug and the polymers.